Firm diversification and earnings management: Evidence from seasoned equity offerings - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2008)
Popular press suggests that diversified firms are more aggressive in managing earnings than non-diversified firms. We examine this claim in the seasoned equity offering (SEO) setting, where firms have been shown to have the incentive to manage earnings upwards. Using the cross-sectional modified Jones [(1991) J Accounting Res 29:193–228] model to measure discretionary current accruals, we find that discretionary current accruals are higher among diversified firms than in non-diversified ones. Our evidence is consistent with the view that the extent of firm diversification is directly related to the degree of earnings management. We further show that diversified issuers with high discretionary accruals underperformed other SEO firms.